Cross-comparison of diagnostic and 0D modeling of a micro-hollow cathode discharge in the stationary regime in an Ar/N2 gas mixture. (6th December 2021) - Remigy, Alice; Kasri, Salima; Darny, Thibault; Kabbara, Hiba; William, Ludovic; Bauville, Gérard; Gazeli, Kristaq; Pasquiers, Stéphane; Santos Sousa, João; De Oliveira, Nelson; Sadeghi, Nader; Lombardi, Guillaume; et al.
Abstract: A micro-hollow cathode discharge (MHCD) operated in Ar/N2 gas mixture, working in the normal regime, was studied both experimentally and with a 0D (volume-averaged) model in this work. This source provides high electron densities (up to 10 15 cm −3 ) at low injected power (1 W). To understand the mechanisms leading to the production of N atoms, the densities of electrons, N atoms and argon metastable atoms (Ar*) were monitored over a wide range of experimental conditions. Electrons, N atoms and Ar* densities were probed by means of optical emission spectroscopy, vacuum ultra violet Fourier transform spectroscopy and tunable diode laser absorption spectroscopy, respectively. Measurements showed that using a smaller hole diameter enables to work with less injected power, while increasing the power density inside the hole and, subsequently, increasing the densities of excited species. Varying the percentage of N2 in the gas mixture highlighted that, up to 80%, the density of N atoms increases although the dissociation rate drops. Looking at the processes involved in the production of N atoms with the help of the 0D model, we found that at very low N2 fraction, N atoms are mostly produced through dissociative electron-ion recombination. However, adding more N2 decreases drastically the electron density. The density of N atoms does not drop thanks to the contribution of Ar* atoms, which are the main species dissociating N2 between 5% and 55% of N2 in the gas mixture. A reasonable agreement is found between the experiments and the model results. This study shows that, with this MHCD, it is possible to significantly modify the production of N atoms when modifying the physical parameters, making it particularly relevant for applications requiring a N atoms source, such as nitride deposition.